Loads bearing mechanism of steel bifurcation combined with concrete anchor block. (1st September 2019) - Su, Kai; Zhu, Hong-Ze; Shi, Yi-An; Wei, Yuan-Ji; Wu, He-Gao; Shi, Chang-Zheng
Highlights: A novel method to calculate the bearing ratio of concrete anchor block is proposed. The hydraulic bifurcation embedded in a concrete anchor block under high water head up to 652 m is analyzed in details. Multiple work conditions of the hydraulic bifurcation are analyzed and compared. Abstract: Bifurcations are employed when two or more branch pipes are merged into one main pipe, which generally located upstream of the powerhouse and embedded in surrounding media. A three dimension (3D) numerical model for the symmetrical Y-shape steel bifurcation with crescent rib embedded in in-situ cast concrete anchor block is developed, in which the water head is as high as 652 m. Then, by means of the point-to-point contact element of CONTAC52 simulating the initial gap between steel pipe and concrete, the resulting distribution of stress, settlement of bedrock are revealed. Further, a novel method to calculate the load bearing ratio of the concrete anchor block is proposed to evaluate the load-bearing capability of the surrounding concrete. Further, this study also discusses the effects of the initial gap, the concrete elastic modulus and the deformation modulus of the bedrock. The results demonstrate adequate rebar should be arranged to ensure the integrity of the anchor block and to limit the crack widths. The design criteria of reinforced concrete penstock are suggested for the detailed design of embedded bifurcations to simplify the construction process, to reduce the steel thickness of the steel bifurcation and the amount of investment.